Wave fields in real media : wave propagation in anisotropic, anelastic, porous and electromagnetic media - Carcione, Jose M. (Handbook of geophysical exploration. Seismic exploration, 2015)
Authored by the internationally renowned Jose M. Carcione, Wave Fields in Real Media: Wave Propagation in Anisotropic, Anelastic, Porous and Electromagnetic Media examines the differences between an ideal and a real description of wave propagation, starting with the introduction of relevant stress-strain relations. The combination of this relation and the equations of momentum conservation lead to the equation of motion. The differential formulation is written in terms of memory variables, and Biot's theory is used to describe wave propagation in porous media. For each rheology, a plane-wave.